Symptoms versus problems (SVP) in household high speed broadband (HSBB): regaining momentum for Unifi, Malaysia - Kader Ali, Noor N; Soon, Bin Y.; Goh, Lee S.; Ahmad Razi, Nur A. (Limited Liability Company “Consulting Publishing Company “Business Perspectives”, 2015)
Problem identification is a talent and skill set required in all leaders. The objective of this study is to reveal an improved research method by integrating mixed-method research combined with problem identification method (using symptoms versus problems (SVP) framework) for telco service providers. The SVP framework discovers the primary causes to the decrease in revenue growth rates. Malaysia’s household broadband penetration rate grew from 15.2% (2007) to 67.1% (2013). Meanwhile, the growth rate for Unifi, offered by Telekom Malaysia (TM), decreased from 104% (2012) to 30% (2013). Why? There are eight causes, specifically; not prioritizing 4G LTE license; obligating social services to rural areas; providing 20-30 Mbps wireless broadband packages by the competitors; offering less competitive price; not covering all zones; offering less favorable service contracts; offering limited packages; and receiving customer complaints. The sequential methodology process began with semi-structured interviews, analysis of unpublished company data, customer survey on 164 respondents and field observation which were all summarized into a root-cause analysis tool called symptoms versus problems framework (SVP). The SVP indicates TM acquired Packed One to overcome HSBB issues; revamp its strategies to product content offering instead of head-on price war; establishing bureaucracy busting team, competitors busting teams on product innovation; collaborating with local broadcasting companies; and developing talent. Interestingly, this study discovers another framework on critical success factors for telco service providers through development of “House of Pillars for Rapid Growth” of TM in Malaysia.